2006
DOI: 10.1051/rnd:2005058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a supplement rich in linolenic acid added to the diet of post partum dairy cows on ovarian follicle growth, and milk and plasma fatty acid compositions

Abstract: -The objective of this study was to determine the effect of a linseed supplement on follicle growth, progesterone concentrations and milk and plasma fatty acids in dairy cows post partum. Sixteen Holstein cows were given a basal total mixed diet plus one of two supplements: control (C; extruded soybeans; n = 8) or linseed (L; extruded linseeds; n = 8). One month after calving oestrous cycles were synchronised (PRID ® ). Follicle growth and milk progesterone concentrations were measured every 2 d over the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
3
18
1
Order By: Relevance
“…Ovaries were monitored by ultrasonography for follicular status, and the average numbers of 2-to 5-mm follicles on d 5 and 9 of the cycle were higher in the cows fed encapsulated flaxseed oil than in those fed sunflower oil, whereas the average numbers of follicles ≥10 mm on d 5, 9, and 13 were higher in those fed sunflower oil than in those fed encapsulated flaxseed oil and controls. In contrast, Ponter et al (2006) reported an increased number of small follicles in cows fed EF compared with those fed extruded soybeans (rich in C18: 2n -6), with no difference in the number of medium-sized or large follicles. Similarly, the number of 3-to 7-mm-diameter follicles collected from cows supplemented with encapsulated flaxseed oil or fish oil during ovum pick-up procedures was higher than that from SFA-fed cows (Moallem et al, 2013).…”
Section: Follicular Dynamics and Estrous Cycle Patternmentioning
confidence: 78%
“…Ovaries were monitored by ultrasonography for follicular status, and the average numbers of 2-to 5-mm follicles on d 5 and 9 of the cycle were higher in the cows fed encapsulated flaxseed oil than in those fed sunflower oil, whereas the average numbers of follicles ≥10 mm on d 5, 9, and 13 were higher in those fed sunflower oil than in those fed encapsulated flaxseed oil and controls. In contrast, Ponter et al (2006) reported an increased number of small follicles in cows fed EF compared with those fed extruded soybeans (rich in C18: 2n -6), with no difference in the number of medium-sized or large follicles. Similarly, the number of 3-to 7-mm-diameter follicles collected from cows supplemented with encapsulated flaxseed oil or fish oil during ovum pick-up procedures was higher than that from SFA-fed cows (Moallem et al, 2013).…”
Section: Follicular Dynamics and Estrous Cycle Patternmentioning
confidence: 78%
“…Formaldehyde treatment of linseeds did not increase milk 18:3n-3 more than raw seeds did [145,146]. Furthermore, the intake of 200-460 g/day of 18:3n-3 from extruded linseeds [128,144,147,148] or extruded rapeseeds 1 linseeds [149] increased the cow milk fat 18:3n-3 percentage by 0.3-0.9 g/100 g FA, i.e. in the range observed above with unprocessed linseeds or oil and lower than what could be obtained with grazing high-quality pastures (see Section 3.1.1.…”
Section: Linolenic Acid and Long-chain N-3 Famentioning
confidence: 89%
“…Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009. The inconsistencies among these studies could be due to differences in the amounts of lipid supplements, duration of supplementation, and season.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%